Microscopy after Colonoscopy: an Institutional experience in India - Balekuduru Chaitanya; B.A. Ramakrishna; Vissa Shanthi; S. Rajasekhar Reddy (International Journal of Medical Research and Review, 2014)
Objectives: To study the histopathological features of mucosal and resected biopsy specimens for etiological diagnosis and comment on the extent, activity and severity of colonic lesions wherever possible by histological examination and correlate with the clinical diagnosis provided.Methods: Consecutive colonic biopsy/resected specimens received during a period of two years were included in this study. Clinical details with laboratory results were correlated with the pathological findings.Results: 124 mucosal biopsies and 56 resected specimens were included in this prospective study. Of 180 patients, 118(65.5%) were men. All age groups from 2-90 years were included in the study. Majority constituted 51-60 years (27.2%). Rectal bleeding was the most common presentation (71.1%) followed by constipation (48.9%). Two patients had normal mucosal biopsy, neoplastic lesion was noted in 78(43.3%) and the remaining majority 100 (55.5%) had non neoplastic etiology. Among non-neoplastic etiology, chronic non-specific colitis was the most common diagnosis (56%) followed by ulcerative colitis (17%) and ischemic colitis (10%). In benign lesions, inflammatory polyps (37.5%) were the commonest followed by tubular (40%) and villous adenomas (10%). Adenocarcinoma was the commonest neoplastic lesion noted in 95% of the patients. Rectum and cecum were the common sites of abnormality. Multiple deep biopsies that the relationship between tumour and stroma could be properly assessed as well as routine biopsies were adequate in 98.9% of the cases.Conclusion: The study was made as an effort to bring into light the spectrum of colonic lesions in a teaching hospital in South India.